2020
DOI: 10.1111/apa.15276
|View full text |Cite
|
Sign up to set email alerts
|

Salivary pepsin A detection related to gastro‐oesophageal reflux episodes in children undergoing impedance probe monitoring

Abstract: Aim: Gastro-oesophageal reflux is routinely diagnosed with invasive intraluminal impedance pH probe monitoring. This study aimed to determine whether gastric pepsin A detected in saliva of children correlates with gastro-oesophageal reflux. Methods: Patients undergoing probe monitoring were prospectively recruited between 2014 and 2016 at a paediatric hospital. Standard impedance and demographic data were obtained from electronic medical records. Salivary samples were collected during impedance and measured fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
(60 reference statements)
0
4
0
Order By: Relevance
“…Evaluation of MII in conjunction with TA pepsin A activity would facilitate the accurate quantification of each reflux episode and provide anatomic characterization of each episode with respect to proximal extent of gastric contents. Recently, salivary pepsin A was associated with GER episode in pediatric patients undergoing MII probe monitoring (43). Further studies evaluating salivary pepsin A in relation to TA pepsin A and MII/ pH studies are warranted to explore the utility of biomarker pepsin A to detect microaspiration.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of MII in conjunction with TA pepsin A activity would facilitate the accurate quantification of each reflux episode and provide anatomic characterization of each episode with respect to proximal extent of gastric contents. Recently, salivary pepsin A was associated with GER episode in pediatric patients undergoing MII probe monitoring (43). Further studies evaluating salivary pepsin A in relation to TA pepsin A and MII/ pH studies are warranted to explore the utility of biomarker pepsin A to detect microaspiration.…”
Section: Discussionmentioning
confidence: 99%
“…Among pepsin A positive samples, 72% of samples corresponded to a gastroesophageal reflux episode. The authors reported that pepsin peak levels were significantly correlated with acid GERD [ 82 ]. The usefulness of pepsin measurement in pediatric patients was supported by Klimara et al in a controlled study where authors compared pepsin saliva measurements between pediatric patients with laryngomalacia and healthy controls [ 38 ].…”
Section: Diagnosticmentioning
confidence: 99%
“…[12][13][14] The gastric enzyme pepsin is present in all refluxate and has been validated as a sensitive and specific marker of EER. [15][16][17][18] MEF pepsin is present in $85% of pediatric ROM and OME cases. 10 The high incidence and predominantly weakly acid nature of EER in OM have been corroborated by pH-multichannel intraluminal impedance testing (pH-MII), which identified 68% incidence of EER in OME with 88% of reflux events >pH 5.…”
Section: Introductionmentioning
confidence: 99%
“…EER is extensively buffered in transit to the airways and is commonly weakly or non‐ acidic, yet airway mucosa is susceptible to damage by nonacid elements of EER and weak to non‐ acid EER is associated with respiratory symptoms in adults and children 12–14 . The gastric enzyme pepsin is present in all refluxate and has been validated as a sensitive and specific marker of EER 15–18 . MEF pepsin is present in ~85% of pediatric ROM and OME cases 10 .…”
Section: Introductionmentioning
confidence: 99%